Model-scale/full scale correlation in open water and ice for Canadian Coast Guard "R-Class" icebreakers - Spencer, D.; Jones, S. J. (2001)
Model scale data from the National Research Council of Canada, Institute for Marine Dynamics for the Canadian Coast Guard's R-Class icebreaker are compared with previous model tests and, more importantly, with three sets of full-scale ice trials data collected in 1978,1979 and 1991. In open water, good agreement between model and full-scale was found for bollard tests, and for self propulsion tests provided a roughness allowance of 0.0008 was used. In ice, good correlation was found with the 1978 tests when the ship was new and there was little snow cover, using a model hull/ice friction coefficient of 0.05. Good agreement with the later tests, 1979 and 1991, was also obtained with somewhat higher model/ice friction coefficients of 0.055 and 0.065. This is attributed to a deteriorating, and hence rougher, full-scale ship hull surface. The model tests showed that a change in friction coefficient from 0.03 to 0.09 causes a doubling of the delivered power. For the full-scale ship, it is suggested that relatively inexpensive localised hull maintenance in the shoulder area, where ice jamming occurs and hence hull/ice friction is important, could improve performance and reduce the chance of structural damage. NRC publication: Yes